Ritual as Rehabilitation: Pentecostal Prison Ministries and the Spiritual Remaking of Incarcerated Bodies in Calabar, Cross River State - Kenneth Onah Odibu; Gabriel Aduma Odey; Gregory Ajima Onah (Universitas Negeri Makassar, 2026)
The prison has emerged as a significant site of Pentecostal expansion in contemporary Nigeria, with churches establishing ministries that conduct worship services, deliverance sessions, and baptismal ceremonies within correctional facilities. This paper examines Pentecostal prison ministries in Calabar, Cross River State, arguing that they represent a distinctive form of spiritual governance operating at the intersection of state power and religious authority. Drawing on the anthropology of religion, the sociology of punishment, and the literature on African Pentecostalism, the paper analyses how Pentecostal practices of deliverance, spiritual warfare, and baptism function as technologies of inmate transformation, constituting a spiritual rehabilitation that complements and sometimes competes with the secular programmes of the Nigerian Correctional Service. The study explores the complex motivations underlying inmates' religious participation, ranging from genuine spiritual seeking to strategic performance designed to secure material benefits and demonstrate rehabilitation for parole boards. It further examines the gender dynamics of prison ministry, the theological justifications offered by Pentecostal pastors for their prison work, and the implications of religiously motivated rehabilitation for understandings of justice and punishment in contemporary Nigeria. The paper concludes that Pentecostal prison ministries represent a significant but understudied dimension of the relationship between religion and the state in Africa, one that challenges secular assumptions about the purposes and practices of incarceration.